Enterprise security : second International Workshop, ES 2015, Vancouver, BC, Canada, November 30-December 3, 2015, Revised selected papers /: second International Workshop, ES 2015, Vancouver, BC, Canada, November 30-December 3, 2015, Revised selected papers. (2017) - Unknown
No abstract available